Problem and dilemma faced by Malaysia contractor when handling international project - Marhazlin, Mohamad (2017)
The exploration of Malaysian contractors into the international construction market is now more than 20 years old which is from 1970.This is due to increase of Malaysia contractors in domestic market which caused number of contract imbalanced. Although Malaysia contractor gaining success in international project, the problem is exportation of these Malaysian contractor services to the international market cannot avoid them from facing the diversion and differentiation of host countries’ which causing problem and dilemma for them. This research, will determined the problem and dilemma faced by Malaysia contractors when handling international project and help them to find alternative in solving this problem and dilemma for the next research. In this research, 50 questionnaires about problem and dilemma had been distributed toward 50 Malaysia contractor which involved with international project. Based on the result, index number, N method had been used to analyse the data and rank each factor in each of problem and dilemma stated. The study has identified that economic and financial aids are the main problem them while construction related risk is main dilemma toward Malaysia contractor.